Identification Of Leading Sectors In Batam: LQ, DLQ, and Shift-Share Analysis - Pascal, Emilio (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2023)
The purpose of this research is to find out which sector is the leading sector in Batam. This research uses LQ, DLQ, and Shift-share Analysis. LQ analysis shows that Processing Industry, Electricity and Gas Procurement, Water Supply, Waste Management, Waste and Recycling, Construction, Transportation and Warehousing, Accommodation, Drinking, and Food Provision, Information and Communication, and Financial and Insurance Services can fulfill domestic needs in Batam and export products from these sectors to other regions. Using DLQ, it is found that Agriculture, Forestry, and Fisheries have the potential for rapid growth and development. Using shift-share, Processing Industry, Construction, Information and Communication, and Financial and Insurance Services have rapid growth rates, good competitiveness, and are progressive. Based on these findings, it is expected that the Batam Government and the Head of BP Batam can focus development on these leading sectors, in order to drive economic growth.